Credit risk management: An imperative for profitability of Centenary Bank Kabale Branch - Aluonzi, Burani; Byamukama, Eliab; Marus, Eton; Charity, Tushemereirwe (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study focuses on establishing the effect of credit risk management on the profitability of the Centenary Bank Kabale Branch. Credit Risk Management was operationalized as credit risk identification, risk assessment, and risk control, while profitability was operationalized as Return on Equity, Return on Assets, and Non-Performing Loans. Research methodology: The study population comprised of 140 respondents. A sample size of 103 respondents was obtained using the Krejcie and Morgan 1970 table for sample determination. This study adopted a mixed method approach.  Quantitative data were collected using Self-Administered Questionnaires and analyzed using Pearson’s linear correlation coefficient. Qualitative data were collected through in-depth interviews and analyzed using content analysis. Results: The findings indicate that the majority of the respondents were male, aged 31–40 years, and bachelor’s degree holders. Risk identification (r=0.882), risk assessment (r=0.776), and risk controls (r=0.829) have a significant positive relationship with profitability at the central bank. Limitations: The limitations include bias from the respondents and the study being conducted in only one branch, making generalization difficult. Contribution:  These investigations have informed Centenary Bank managers of the importance of credit risk identification, risk assessment, and risk control. Managers should focus on mitigation measures to reduce risks, create a credit risk assessment team to evaluate risks, establish strategies, and prioritize risk management practices by implementing policies in place. The findings contribute to the literature on credit risk management in terms of the central bank. Novelty: Previous similar research only studied how environmental accounting is implemented in a hospital and did not compare its implementation before, during, and after a pandemic.